Pós-colheita de cogumelos shimeji brancos in natura submetidos à radiação UV-C e cloreto de cálcio - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The post-harvest life of edible mushrooms is limited by the accelerated spoilage and development of pathogens, culminating in the senescence of the fruit which is characterized by rapid browning and softening. Thus, the objective was to evaluate the post-harvest of in natura white shimeji mushrooms subjected to different doses of UV-C radiation and calcium chloride concentrations. Two experiments were carried out in a completely randomized design (DIC), in both experiments a 5x8 factorial scheme was used, the first: 5 doses of UV-C radiation x 8 days of analysis, and the second: 5 concentrations of CaCl2 x 8 days of analysis, containing 3 replicates, with 70±1 grams of mushrooms. In the first experiment, the fruits were exposed to different doses of UV-C radiation, as follows: 0 (control), 1, 2, 3 and 4 kJm-2, while for the second, the fruits were immersed in different concentrations of chloride of calcium, as follows: 0% control – immersed in distilled water; 1%, 2%, 3% and 4% CaCl2. Both were stored for 14 days (0, 2, 4, 6, 8, 10, 12 and 14 days), with analyzes every 2 days. All experimental units were stored in polyvinyl chloride (PVC) + expanded polystyrene (EPS) packaging in a B.O.D. (Biochemical Oxygen Demand) at 2±0.5°C and 60±3.8% RH for UV-C and 51±5% RH for CaCl2. The parameters evaluated were: mass loss, firmness, soluble solids, hydrogenic potential, color (brightness, chroma, °hue, darkening index, whiteness index and color difference), total antioxidant activity (DPPH and ABTS) and total extractable polyphenols. Data were subjected to permutational multivariate analysis of variance (PERMANOVA) (P≤0.05) and, when significant, were demonstrated by means of dendrogram and principal component analysis (PCA), using a Euclidean distance matrix. For the first experiment there was no significance for the interaction, neither for the days factor, only for the UV-C radiation doses factor. The UV-C radiation doses formed 3 groups, according to the similarities of their behavior through the variables. Already in relation to PCA, among the doses applied, the dose of 2 kJm-2 proved to be effective in maintaining the quality of mushrooms with greater luminosity, greater whiteness, greater amount of total extractable polyphenols and total antioxidant activity. On the other hand, the dose of 3 kJm-2 presented undesirable characteristics, as well as a higher browning index, color and chroma difference, consequently darker mushrooms and unsuitable for consumption. It is concluded that the dose of 2 kJm-2 was effective in maintaining the postharvest quality of white shimeji mushrooms. In the second experiment, it was observed that the concentrations of calcium chloride were separated by groupings, according to the performances presented, regarding the quality of the mushrooms. Among the concentrations applied to edible mushrooms, the doses of 2 and 3% ensured the maintenance of firmness and preservation of the light color. The other concentrations had greater mass loss, greater color difference and darker mushrooms. It was concluded that the concentrations of 2 and 3% were effective in maintaining the postharvest quality of white shimeji mushrooms until the 8th day, providing light coloration. The doses of 0, 1 and 4% of calcium chloride remained close to the final days of storage, namely: 10, 12 and 14th day, which is characterized by darker mushrooms with lower quality of sale.
Postharvest of in natura white shimeji mushrooms submitted to UV-C radiation and calcium chloride
Keywords: Armazenamento; Cálcio; Fungos comestíveis; Irradiação; Pleurotus ostreatus; Vida útil; Storage; Calcium; Edible fungi; Irradiation; Pleurotus ostreatus; Shelf life; Cogumelos comestíveis; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA